Board Structure and Bank Performance: The Mediating Role of Intellectual Capital - Nikolić, Jelena; Erić Nielsen, Jelena; Peković, Jelena (Naše gospodarstvo/Our economy, 2022)
Intellectual capital in the knowledge era is a strategic advantage of board structure, which leads to the improvement of a company’s work and the achievement of its goals. The aim of this study is to develop a structural model that connects the corporate governance, intellectual capital and financial performance of the banking sector. Corporate governance is conceptualised by the board of directors as the main internal mechanism of corporate governance, which is measured by the size of the board of directors, the number of independent board members and the female board members. Intellectual capital represents a mediator in this model and its efficiency is calculated through the Value Added Intellectual Coefficient (VAIC) model, while the financial performance of banks is measured through return on assets (ROA) and return on equity (ROE). The results of the study conducted in 22 Serbian banks between 2015 to 2019 show that the size of the board of directors and the number of independent board members have a statistically significant impact on intelectual capital (IC), but there is no impact on total assets (ROA). The number of women in the board of directors does not have a statistically significant effect on either ROA or ROE. The findings also indicate that intellectual capital (HCE, SCE, CEE) has a significant mediating role in the relationship between board structure and bank performance. The results of this study will provide a significant contribution to further investment in intellectual capital as the strongest link in achieving positive effects on bank performance.
Keywords: corporate governance; board of directors; board structure; intellectual capital; financial performance; banking sector